PERANAN SISTEM INFORMASI MANAJEMEN DALAM PENGGUNAAN E-COMMERCE DAN KEMUDAHAN PELAYANAN KONSUMEN PT KERAMIKA INDONESIA ASSAOSIASI (KIA) - Rulis Setyowati; Hwihanus Hwihanus (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The emergence of the information age globally has resulted in a dynamic model shift in society. The field of technology is one of the characteristics of a modern society known as the information society. But not everyone is proficient in managing data. In other words, there are still some demographics who don't recognize the value of science. A new concept known as a Management Information System (MIS), which is characterized by the principles and various supporting features necessary to build an enterprise management information system, is developing in the information field as a reaction to this phenomenon. It goes without saying that wanting to expand a business can make it more profitable. A marketing strategy that utilizes electronic media E-commerce in particular is something that needs to be done. a system that makes it easy for users and customers to use services in buying and selling transactions. E-commerce, or electronic commerce as it is known in Indonesia, is the act of distributing, selling, buying and marketing something (goods and services) through the use of telecommunications networks such as the internet, television or other computer networks. E-commerce is the act of buying and selling products online. Over the past few years, e-commerce has expanded and eventually displaced traditional (offline) merchants.